Clinical and radiological evaluation of maxillofacial and otorhinolaryngological manifestations of Hansen’s disease - Rachel Bertolani do Espírito Santo; Rachel Azevedo Serafim; Rafael Maffei Loureiro; Dâmaris Versiani Caldeira Gonçalves; Daniel Vaccaro Sumi; Ricardo Andrade Fernandes de Mello; Simon M. Collin; Patrícia D. Deps (Scientific Reports, 2022)
Abstract To characterize maxillofacial, otorhinolaryngological and oral manifestations of Hansen’s disease (HD), we conducted a cross-sectional study in 21 current patients attending the Unidade Básica de Saúde de Jardim América, Espírito Santo, Brazil and 16 former patients resident at Pedro Fontes Hospital using data from computed tomography imaging, rhinoscopy, and oroscopy. Maxillofacial characteristics were compared with 37 controls. Differences in bone alterations across the three groups were determined mainly by severe resorption/atrophy being more frequent in former HD patients, with severe resorption/atrophy of the anterior alveolar process of maxilla in 50.0% (8/16) of former patients, 28.6% (6/21) of current patients and 10.8% (4/37) of controls and of nasal bones and aperture in 31.3% (5/16) of former patients compared with 0/21 current patients and two controls. There were no substantial differences in otorhinolaryngological and oroscopic findings between the two patient groups. HD patients had more tooth loss than the age-matched control group. Maxillofacial, otorhinolaryngological and oroscopic finding scores were strongly correlated only in current HD patients. Correlation between otorhinolaryngological and maxillofacial scores suggests that protocols for HD patient assessment and follow-up could include otorhinolaryngological evaluation, with radiological imaging where necessary, subject to replication of our findings in a larger study.